Effect of boron doping on grain boundary cohesion in technically pure molybdenum investigated via meso-scale three-point-bending tests. (June 2023) - Jakob, S.; Hohenwarter, A.; Lorich, A.; Knabl, W.; Pippan, R.; Clemens, H.; Maier-Kiener, V.
Abstract: Molybdenum has numerous advantageous functional and high-temperature properties. However, plastic deformation as well as structural applications are limited due to a propensity for brittle, intercrystalline failure, especially at low temperatures. It is well known that oxygen segregations have a detrimental effect, whereas it is assessed that carbon and/or boron have a beneficial effect on grain boundary cohesion. An advanced approach for the improvement of these interfaces is segregation engineering, e.g. the addition of cohesion enhancing elements segregating to the grain boundaries. To investigate early stages of crack formation, three-point bending tests on recrystallized commercially pure and boron micro-doped molybdenum were conducted between −28 °C and room temperature. The tensile-loaded top surface of the specimens was examined post-mortem close to the final fracture area via scanning electron microscopy. The occurring separations of grains are investigated for distinct features and the chemical composition of the interface is complementary measured by atom probe tomography. Highlights: Grain boundary cracks were investigated on the tensile-loaded sample surface after bending. Doping with B reduces the relative length of separated interfaces significantly. Transcrystalline cracks occur mostly during final catastrophic failure of the samples.